تعليم كتابة الإنشاء باستخدام الصور التعليمية - Nur Thoifah (Institut Agama Islam Negeri (IAIN) Metro, 2017)
Among the language skills, writing is the highest skill of the four language skills (Listening, Speaking, Reading, Writing), where the learning process with multiple levels that can be started from dictation to composition. Composition is the last level of writing and the most difficult stages in language learning. In it, students need to exert all his energy, physical as well as his thoughts, because composition is expressing thoughts in writing. Given the difficulty of studying composition, then the media needs to be easier to learn, one of which is the picture of learning, because it is a medium of learning that can lead to appeal to students, it can facilitate students' understanding, to ease of explanation that are abstract, to clarify the important parts, and easier for students to reveal the contents of his thoughts into written form. Key words: Learning, Composition, Picture of Learning